Factores de riesgo de retinopatía diabética en pacientes con diagnóstico de diabetes mellitus - Guanilo Reyes, Chris Katherine (2018)
Diabetes mellitus type 2 (DM2) is a systemic disease with microvascular complications such as diabetic retinopathy (DR), which affects retinal arterioles, capillaries and precapillary venules, and may even reach blindness. Objective: To determine the risk factors for diabetic retinopathy in patients with type 2 diabetes mellitus at the Belen Hospital of Trujillo (BHT). Methods and materials: Observational, analytical study, case and control design. The population was conformed by patients with diagnosis of DM2 of the BHT, in the period 2010 - 2015. There were 78 cases and 156 controls, being the cases patients with DR. Results: In the statistical analysis with DR we found: the prolonged time of DM2, OR: 2.74 (CI: 95%: 1.57 - 4.78), poor glycemic control, OR: 2.54 (CI: 95%: 1.43 - 4.49) and arterial hypertension OR: 2.28 (CI: 95%: 1.3 - 3.97). No significant association was found with obesity, dyslipidemia, family history of DM2 (FHDM2) and smoking habit. Conclusion: In the present study, the prolonged time of evolution of DM2, poor glycemic control and hypertension constituted risk factors for diabetic retinopathy in patients treated in the BHT in the period 2010-2015, while obesity, dyslipidemia, FHDM2 and smoking habit did not were